Prevalence of ocular abnormalities in prediabetic patients - Sokołowska-Oracz, Anna; Litwińczuk-Hajduk, Joanna; Piątkiewicz, Paweł (Klinika Oczna / Acta Ophthalmologica Polonica, 2016)
Aim : The aim of our study was to evaluate the prevalence of ocular abnormalities in prediabetic individuals. Material and Methods : 61 subjects aged 37–78 (41 women, 20 men), with impaired fasting glucose and/or impaired glucose tolerance, were enrolled in the study and compared to 30 healthy volunteers, aged 39–75 (20 women, 10 men), without prediabetes and history of previous ocular diseases. Both groups of patients underwent a complete physical examination, biochemical tests and ophthalmic examination: visual acuity testing, intraocular pressure measurement, anterior and posterior segment evaluation, fundus photographs, optical coherence tomography, colour vision and letter contrast sensitivity tests. Results : The prevalence rates of various ocular abnormalities in prediabetic subjects as compared to healthy controls were as follows: acquired colour vision impairment 8.2% vs. 0% (p<0.05), signs of retinopathy: 9.8% vs. 0% (p<0.05), cataract: 32.8% vs. 6.7% (p<0.05), and corneal surface disorders: 19.7% vs. 3.3% (p<0.05). Optical coherence tomography revealed increased prevalence of posterior vitreous detachments and epiretinal membranes in prediabetic individuals as compared to healthy controls. There were no statistically significant differences in central retinal thickness, mean visual acuity and mean intraocular pressure between the two groups. Conclusion : Patients with prediabetes present with numerous ocular abnormalities. The prevalence of ocular disorders in prediabetic subjects is significantly higher as compared to healthy population. Regular ophthalmic monitoring seems to be essential at this stage of hyperglycemic disorders. A dedicated prevention and screening programs should be implemented in prediabetic population in order to early detect ocular abnormalities and identify individuals at risk of other diabetic complications.